ARANA, Aitor. Izarbeibarko Hiztegia. Nafarroako Gobernua, Hiria: argit. 2002 urtea, 162 or. - Mujika, Luis Mari (EGAN, 2021)
LUIS MARI MUJIKA: ARANA, Aitor. Izarbeibarko Hiztegia. Nafarroako Gobernua, Hiria argit. 2002 urtea, 162 or.